Optimal scheduling to minimize noise exposure in an oil and gas field. (April 2019) - Atanas, Jean-Pierre; Simmons, Rodney; Rodrigues, Clarence
Noise analysis with different scenarios has been conducted for an oil and gas field to determine whether workers during sandblasting operations were fully protected from high noise to prevent ear injuries and downtime. The main purpose is to minimize noise doses affecting workers through an optimal scheduling algorithm. Data collected from a noise meter was fully evaluated and analyzed in terms of LAeq —A-weighted average energy equivalent sound pressure levels—and Lpk energy peak, in the audible range from 12.5 Hz to 20 kHz based on the one-third octave band frequencies. All noise results were found above the maximum permissible exposure limit 85 dB(A). Another important feature is the sharp rise observed in all weighted levels up to a mean value of 67 dB at low frequency of 80 Hz. A sharp decrease in the high frequency noise levels beyond 8 kHz is also observed. Comparisons between different scenarios are also presented. Additional noise sources such as compressors and air coolers add up an important fraction of the workers' noise exposure dose and highly contribute to the hearing loss. Finally, a fair scheduling algorithm to optimize noise exposure time by minimizing the noise dose is proposed.